The Mediating Effect of Patient Satisfaction in The Effect of Service Quality on Patient Loyalty: Patient Survey at Hermina Hospital Bandung Pharmacy Installation - Aurora Rahyu Pasya (PT. Publikasiku Academic Solution, 2024)
Background: Pharmaceutical services are a form of health service that directly connects patients with pharmaceutical preparations. The quality of service greatly determines the level of patient satisfaction. Service quality and patient satisfaction are factors that influence patient loyalty. Method: The data analysis technique that will be used to test this research uses the Partial Least Square (PLS) method which is operated using SMARTPLS 4.0. Results: Service quality has a significant effect on patient satisfaction and patient loyalty, patient satisfaction has a significant effect on patient loyalty, and service quality has a significant effect on patient loyalty which is mediated by patient satisfaction. Conclusion: When a hospital provides better quality service than before, it will have an impact on high patient satisfaction and patient loyalty. The more positive patient satisfaction is, the more patient loyalty will increase. When service quality is improved, a positive perception of patient satisfaction arises, which can encourage increased patient loyalty.